International Brigade. British Battalion : trade unionist members (list) (1938)
1938 034-0094-003 -2- H. Hunter. 66 Grove St, Belfast, I.A.W.U. W. Leakey. 53 Kingsmead St, Bath. G.M.W.U. EC Trades Council. M. Lehane. Morley Bridge Kilgaroon Co.Kerry. W.U.T. E. McIlroy. Club Hotel Derby. N.U.S. R. Mortimer. 10 Alexander Place, Hull, G.M.W.U. W. Ryder. 18 Bowood Road, Sheffield, N.P.U., 3 months. 292/946/34/94(iii)